Meningkatkan Literasi Membaca Siswa Melalui Implementasi Program KKN di SMP Katolik Adisucipto Penfui Kupang - Yohana Imelda Harapan; Yasinta Gonda Beka; Pastelina Susanti Dendo; Theodosius Donga; Mikhael Oktovianus Beno Baba (Pandawa : Pusat Publikasi Hasil Pengabdian Masyarakat, 2025)
Abstract and Keywords must be written in English, in italic style, and contain a brief description of the research background, objectives, methods, findings, and implications. The abstract is written in one paragraph with a single space (maximum 200 words), without any reference or formula. Real Work Lectures (KKN) is a mandatory program for students which aims to apply knowledge in society. This report presents the results of the implementation of KKN at Agustinus Adisucipto Catholic Middle School, Penfui, which focused on creating a spiritual literacy corner. This activity aims to increase students' reading interest and spiritual understanding, as well ascreating a more comfortable learning environment Through various activities, students succeeded in developing literacy facilities which had a positive impact on the teaching and learning process at school. The results of this activity show that with the existence I of a literacy corner, students are more enthusiastic in learning and can overcome learning obstacles in class.